DIVERSIFICATION OF WHITE OYSTER MUSHROOM (PLEUROTUS OSTREATUS) BAGLOG MEDIA WITH THE ADDITION OF PALM SAP WATER EXTRACT AND QUICKLIME BASED ON DIFFUSIVE MIXING TECHNOLOGY - Genta Darmawan; Armaniar; Maimunah Siregar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Mushroom growth is influenced by various additional nutrients given, including the addition of quicklime and palm sap water extract. The purpose of this study was to determine the addition of quicklime and palm sap water extract to the baglog media on the growth of white oyster mushrooms (Pleurotus ostreatus) and the interaction between the two. The study was conducted from January 2024 to April 2024 in laboratory rooms C106 and C108, Panca Budi Development University, Medan, Jl. Gatot Subroto Medan. The research method used a factorial Completely Randomized Design (CRD) consisting of 2 factors, 16 treatments, 3 replications, and 96 baglogs. The first factor has 4 treatment levels, namely: K0: 0 g/baglog, K1: 15 g/baglog, K2: 20 g/baglog and K3: 25 g/baglog. The second factor has 4 treatment levels, namely: N0: 0 ml/baglog, N1: 10 ml/baglog, N2: 15 ml/baglog and N3: 20 ml/baglog. The parameters observed were the rate of mycelium growth (cm), number of mushroom stalks, height of mushroom stalks (cm), diameter of mushroom caps (cm), thickness of mushroom caps (mm), number of mushrooms (Clumps), and fresh weight of mushrooms/baglog (g).The results of the mycelium growth rate data were highest in the treatmentK3as big as19.57cm. The results of the highest number of stems in the treatmentK37.96 sprigs. The highest data stem height results were in the K treatment3as big as9.61cm. The highest data cap diameter results were in treatment K3as big as22.57cm. The highest data hood thickness results were in treatment K3of 8.14 mm. The highest number of fungi (clumps) data was in the K treatment.3of 7.96 clumps. The highest fresh weight of mushrooms/baglog (g) was in the K treatment.3as much as 200.60 g.